123k views
14 votes
2x-y=60
6y=x
Solve the system using substitution. Check your solution.

User BBoom
by
5.0k points

1 Answer

0 votes

Answer:


x = (360)/(11)


y = (60)/(11)

Explanation:

Since 6y=x plug 6y in for x on the top equation.


2(6y) - y = 60


12y - y = 60


11y = 60


y = (60)/(11)

Plug y=60/11 into 6y=x


6( (60)/(11) ) = x


(360)/(11) = x

Plug 360/11 into 2x-y=60


2( (360)/(11) ) - (60)/(11) = 60


(720)/(11) - (60)/(11) = 60


(660)/(11) = 60

The identity is true

User Freddie Chopin
by
5.7k points